INDEX ONOMASTIQUE/AUTHOR INDEX - Alley, Doreen; Bornes, Christian; Brodie, Nancy; Brown, Jack E.; Bussy, Didier; Caya, Marcel; Carroll, John M.; Deschatelets, Gilles; Deslauriers, Paul E.; Francois, Jean L.; Gastaldy, Suzanne; Granda, Sally; et al. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF